Danggui buxue tang inhibited mesangial cell proliferation and extracellular matrix accumulation through GAS5/NF-κB pathway. Issue 10 (18th October 2019) - Zhang, Rui; Han, Xiao; Huang, Tao; Wang, Xiuge
Abstract: Diabetic nephropathy (DN) is the common complications of diabetes mellitus, but the efficacy of available treatments for the prevention of DN is still unsatisfactory. In the present study, we aimed to explore the effect of Danggui buxue tang (DGT) on the proliferation of high glucose (HG)-induced mesangial cells and accumulation of extracellular matrix in mesangial cells. We found DGT up-regulated the expression of growth arrest specific transcript 5 (GAS5) and IκB kinase (IKK) dose-dependently in mouse mesangial cells (SV40 MES-13). We found DGT regulated the expression IKK and the activity of nuclear transcription factor-κB (NF-κB) via GAS5, and proved that long non-coding RNA (lncRNA) GAS5 was positively related with IKK. And we proved GAS5 regulated the expression of IKK and the activity of NF-κB. In addition, DGT inhibited the viability of MES-13 cells and extracellular matrix-related proteins (laminin (LN), fibronectin (FN) and collagen IV (Col IV)) via GAS5. Moreover, we proved GAS5 regulated the viability of SV40 MES-13 cells and extracellular matrix-related proteins through NF-κB pathway. DGT inhibited the proliferation of mesangial cells and accumulation of extracellular matrix via GAS5/NF-κB, therefore, DGT could be an effective treatment for the prevention of DN.